Biotransformation of papaverine and in silico docking studies of the metabolites on human phosphodiesterase 10a. (March 2021) - Eliwa, Duaa; Albadry, Mohamed A.; Ibrahim, Abdel-Rahim S.; Kabbash, Amal; Meepagala, Kumudini; Khan, Ikhlas A.; El-Aasr, Mona; Ross, Samir A.
Abstract: The metabolism of papaverine, the opium benzylisoquinoline alkaloid, with Aspergillus niger NRRL 322, Beauveria bassiana NRRL 22864, Cunninghamella echinulate ATCC 18968 and Cunninghamella echinulate ATCC 1382 has resulted in O-demethylation, O-methylglucosylation and N-oxidation products. Two new metabolites (4″-O-methyl-β-D-glucopyranosyl) 4′-demethyl papaverine and (4″-O-methyl-β- D -glucopyranosyl) 6-demethyl papaverine, (Metabolites 5 and 6) together with 4′-O-demethylated papaverine (Metabolite 1), 3′-O-demethylated papaverine (Metabolite 2 ), 6-O-demethylated papaverine (Metabolite 3) and papaverine N-oxide (Metabolite 4) were isolated. The structure elucidation of the metabolites was based primarily on 1D, 2D-NMR analyses and HRMS. These metabolism results were consistent with the previous plant cell transformation studies on papaverine and isopapaverine and the microbial metabolism of papaveraldine. In silico docking studies of the metabolites using crystals of human phosphodiesterase 10a (hPDE10a) revealed that compounds 4, 1, 6, 3, and 5 possess better docking scores and binding poses with favorable interactions than the native ligand papaverine. Graphical abstract: Structure of papaverine and its metabolite from different Fungi and the Docked poses of the five papaverine-based biotransformation products with better docking scores than the native ligand in the Human PDE-10 A crystal structure. Image 1 Highlights: Biotransformation of papaverine. Seventy-two strains of filamentous fungi of different classes were used in the initial screening of papaverine. Two new metabolites together with other 4 metabolites were isolated. In silico docking studies of the metabolites using crystals of human phosphodiesterase 10a (hPDE10a).